Chromosome-level reference genome assembly provides insights into the evolution of Pennisetum alopecuroides - Teng, Ke; Guo, Qiang; Liu, Lingyun; Guo, Yidi; Xu, Yue; Hou, Xincun; Teng, Wenjun; Zhang, Hui; Zhao, Chunqiao; Yue, Yuesen; Wen, Haifeng; Wu, Juying; et al. (Frontiers in Plant Science, 2023)
Pennisetum alopecuroides is an important forage grass resource, which plays a vital role in ecological environment improvement. Therefore, the acquisition of P. alopecuroides genome resources is conducive to the study of the adaptability of Pennisetum species in ecological remediation and forage breeding development. Here we assembled a P. alopecuroides cv. 'Liqiu' genome at the chromosome level with a size of approximately 845.71 Mb, contig N50 of 84.83Mb, and genome integrity of 99.13% as assessed by CEGMA. A total of 833.41-Mb sequences were mounted on nine chromosomes by Hi-C technology. In total, 60.66% of the repetitive sequences and 34,312 genes were predicted. The genomic evolution analysis showed that P. alopecuroides cv. 'Liqiu' was isolated from Setaria 7.53–13.80 million years ago and from Cenchrus 5.33–8.99 million years ago, respectively. The whole-genome event analysis showed that P. alopecuroides cv. 'Liqiu' underwent two whole-genome duplication (WGD) events in the evolution process, and the duplication events occurred at a similar time to that of Oryza sativa and Setaria viridis. The completion of the genome sequencing of P. alopecuroides cv. 'Liqiu' provides data support for mining high-quality genetic resources of P. alopecuroides and provides a theoretical basis for the origin and evolutionary characteristics of Pennisetum.